Faktor Geografi Tempat Tinggal, Sosial dan Kultural terhadap Pernikahan Dini - Ayudita Ayudita (Universitas Muhamadiyah Manado, 2023)
Early marriage can have negative impacts on reproductive health and the lives of those involved. This study in South Bangka Regency aimed to analyze the relationship between geographic and socio-cultural factors and early marriage. Using a cross-sectional design and Chi-Square statistical test with a 95% confidence level (ρ ≤0.05), the study found that geographic factors did not significantly relate to early marriage (p=0.102). However, logistic regression analysis indicated that female adolescents living in coastal areas had a 1.49 times higher risk of early marriage compared to those living on the mainland. Socio-cultural factors, particularly education, showed a significant relationship (p=0.016), with lower education levels correlating with a higher likelihood of early marriage. Conversely, ethnicity did not show a significant relationship (p=0.147). Although cultural factors were not statistically significant, traditions and cultural norms still influence marriage decisions. Therefore, enhancing education, increasing awareness of the negative impacts of early marriage, and community interventions are crucial. Health professionals are advised to improve education and counseling on reproductive health and the effects of early marriage, adopt a proactive approach in communities, especially in coastal and isolated areas, and collaborate with schools and community organizations. Regular training and effective monitoring systems are also necessary to ensure the success of early marriage prevention programs